Prostatic Metaplasia of the Vagina and Uterine Cervix: An Androgen-associated Glandular Lesion of Surface Squamous Epithelium. (August 2020) - Anderson, William J.; Kolin, David L.; Neville, Grace; Diamond, David A.; Crum, Christopher P.; Hirsch, Michelle S.; Vargas, Sara O.
Abstract : Prostatic-type differentiation in the lower female genital tract is encountered rarely and its causes and clinical associations are not well established. Within the vagina, reports to date have invariably described ectopic prostatic-type differentiation as restricted to the lamina propria. We recently encountered a patient receiving testosterone for gender dysphoria whose vaginectomy specimen showed a prostatic glandular proliferation within the surface epithelium. To elucidate its potential association with androgen exposure, we sought similar lesions, resected over a 26-year period, from patients with exogenous or endogenous androgen excess. Thirteen cases were identified, involving the vagina (n=12) and exocervix (n=1). The most common clinical context was gender dysphoria with long-term testosterone therapy; the lesion was present in 7 of 8 gender-dysphoric patients examined. Four other patients had congenital disorders of sexual development associated with endogenous androgen excess (congenital adrenal hyperplasia, 46, XY disorder of sexual development, and ovotesticular disorder of sexual development). Two had no known exposure to androgen excess. Immunohistochemically, glands stained for NKX3.1 (100% of cases), androgen receptor (100%), CK7 (92%), and prostate-specific antigen (69%). Follow-up (median duration, 11 mo) showed no masses or neoplasia. We propose the designation "androgen-associated prostatic metaplasia" for this form of prostate tissue with distinctive clinical, histologic and immunohistochemical features. It is novel and previously unrecognized within the vagina. It is strikingly prevalent among patients undergoing gender-affirming surgery, an increasingly common procedure. Recognition is important to distinguish it from other potentially neoplastic glandular lesions and facilitate accrual of more follow-up data to better understand its natural history.